Effect of Ni-nanoparticles decoration on graphene to enable high capacity sodium-ion battery negative electrodes. (1st October 2017) - Pramudita, James C.; Pontiroli, Daniele; Magnani, Giacomo; Gaboardi, Mattia; Milanese, Chiara; Bertoni, Giovanni; Sharma, Neeraj; Riccò, Mauro
Abstract: Modification of graphene has been undertaken in many research contexts in order to improve its properties. In this study, we examine Ni-nanoparticles decoration on graphene and its effect on sodium-ion battery performance. A definite trend is observed on the relationship between Ni-nanoparticles concentration (and hence size) and battery performance. Comparable capacities on the order of 420 mAhg −1 after 20 cycles at 100 mAg −1 is observed for the 3 relatively high Ni-concentration samples NiC10, NiC40, and NiC80 . As the Ni:C ratio decreases, a decreasing trend is observed in the measured capacity, with NiC200, NiC500, and NiC1000 producing capacities of 350 mAhg −1, 380 mAhg −1, and 300 mAhg −1 respectively after 20 cycles at the same rate. Ex situ energy dispersive X-ray spectroscopy, scanning, and transmission electron microscopy shows the morphology of the Ni-nanoparticles decorated graphene and assists in quantifing their sodium content, emphasizing the increasing sodium content with increasing Ni-nanoparticles concentration. This systematic study details how Ni-nanoparticles concentration on graphene surfaces can be manipulated to enhance electrochemical performance, and that higher concentrations up to NiC10 favour better performance. For a compromise between performance and cost (Ni cost), the best composition is NiC500 which favors best performance with the least Ni decoration.